2009
DOI: 10.1111/j.1420-9101.2009.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of and strong single gene (Pgi) effects on life‐history traits in the Glanville fritillary butterfly

Abstract: We estimated broad‐sense heritabilities (H2) of 13 female and seven male life‐history traits of the Glanville fritillary butterfly (Melitaea cinxia) under semi‐natural conditions in a large outdoor population cage. The analysis was based on full‐sib families collected as young larvae in the field and reared under common garden conditions. We found significant genetic variance in female lifespan, fecundity, number of matings and host‐plant preference as well as in male body mass and mobility. Apart from host‐pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 51 publications
4
41
1
1
Order By: Relevance
“…This is consistent with the results of Klemme and Hanski (Klemme and Hanski, 2009), who found the same association of Pgi_111 with longevity in females but not in males. Saastamoinen et al (Saastamoinen et al, 2009) have reported a significant effect in both sexes, but the effect was stronger in females.…”
Section: Pgi Genotype Metabolic Rate and Lifespansupporting
confidence: 82%
“…This is consistent with the results of Klemme and Hanski (Klemme and Hanski, 2009), who found the same association of Pgi_111 with longevity in females but not in males. Saastamoinen et al (Saastamoinen et al, 2009) have reported a significant effect in both sexes, but the effect was stronger in females.…”
Section: Pgi Genotype Metabolic Rate and Lifespansupporting
confidence: 82%
“…Host preference is a key driver of habitat use in phytophagous insects such as butterflies, and there is strong evidence both for a heritable component to host plant preference [1,[20][21][22] as well as for its rapid evolution [23]. Range expansion should therefore involve the spread of generalist phenotypes, which will, in turn, cause a shift in population ecology from local-to regional-scale adaptation in the new parts of the range.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, PGI can be considered a gene of large and pleiotropic effects (see also Orsini et al 2009, Klemme & Hanski 2009). In another Fig.…”
Section: Genetic Make-up Of Thermal Adaptation In Lycaena Tityrusmentioning
confidence: 99%